Investigation of 7-benzylidenenaltrexone derivatives as a novel structural antitrichomonal lead compound. Issue 21 (1st November 2015) - Kutsumura, Noriki; Nakajima, Ryo; Koyama, Yasuaki; Miyata, Yoshiyuki; Saitoh, Tsuyoshi; Yamamoto, Naoshi; Iwata, Satoshi; Fujii, Hideaki; Nagase, Hiroshi
Graphical abstract: Abstract: We evaluated antitrichomonal effects of δ opioid receptor (DOR) agonists and antagonists. Although all the agonists were inactive, the DOR antagonists BNTX (2a ) and its derivatives2b –d showed antitrichomonal activity with MIC of 20–40 μM. In addition, the development of a more effective synthetic method for the BNTX derivatives was achieved by using the Knoevenagel condensation.